1- Re-appropriating Matrifocality: Endogeneity and African Gender Scholarship - Adésínà, Jìmí O. (African Sociological Review, 2010)
A central concern of many Southern sociologists has been the crisis ‘intellectual dependence’ (Alatas 2000). Averting what Hountondji (1997) refers to as ‘extraversion’ involves separat- ing what is idiographic in western social science scholarship from its nomothetic aspirations; what chakrabathy (2000) called ‘provincializing europe.’ It involves excavating local ‘li- braries’ (Zeleza 2006b) and scholarship that takes its ‘locale’ or research site on its own terms. ‘The study of Africa’, Oyewumi (2004) argued, ‘must start with Africa.’ In this paper, we ex- plore the works of Ifi Amadiume and Oyeronke Oyewumi as such ventures in endogeneity, and examples of the contribution that African sociologists make when they take their ethnographic data on its own terms; without status anxiety. we examine the contributions of Amadiume and Oyewumi to gender scholarship, focusing on the idea of matrifocality or matricentricity. while not a new concept, the idea of matrifocal or matricentric societies acquires distinct valency in their epistemic framework and as the basis for theorising matriarchy. Rather than an exercise in the archaeology of a ‘mythical pre-historic past’ (eller 2000), matricentricity in Amadiume’s works accounts for the structural and ideo- logical conditions of many African societies. It affords us the basis for transcending the ‘bio- logic’ (Oyewumi 1997) of dominant western feminist discourses. Beyond the epistemic rupture that it produces in gender Studies, we argue that the concept of matrifocality has wider heu- ristic value. we illustrate its theoretical value for rethinking ‘Identity’, beyond the prevailing patricentric framing, and in allowing us to make sense of contemporary African data.